EFL learners’ task-generated interactive discourse / Hazleena binti Baharun - Baharun, Hazleena (2015)
This study investigated the use of different communicative tasks in promoting oral language development among English as a foreign language (EFL) learners in a Malaysian setting. It also examined the nature of oral discourse generated through the use of three distinct communication task types i.e. information-gap, jigsaw and decision-making. Eighteen EFL undergraduates from a public university participated in this study. Full learner interactions recorded during the execution of each task type were transcribed verbatim. The oral discourse was then qualitatively analysed with a special focus on episodes of negotiated interactions, language related episodes (LREs) and learners’ uptake of language input. The findings showed that learners generated episodes of negotiated interactions when engaged in all three task types. However, the depth of the negotiated interactions differed between the different tasks. When engaged in the information-gap task completion, they demonstrated a procedural approach which included interaction episodes related to handling, organising and executing the task. However, when engaged in the jigsaw and decision-making task completion, they demonstrated an exploratory approach resulting in episodes of joint meaning-making, joint investigation, questioning and reasoning, problem solving and intense negotiation. In addition, data indicated emergence of collaborative dialogues and LREs in the learner interactions especially in the jigsaw and decision-making task types. The results of this study seem to provide empirical evidence that language communication tasks do promote meaningful interactions among Malaysian EFL undergraduates. Data clearly showed widespread generation of interaction episodes during task completion which evolved into LREs and became uptake of language input. These strongly suggest the existence of language learning opportunities and possibility of language development. Language communication tasks when effectively executed in a tertiary EFL setting can encourage meaningful oral discourse and expose learners to novel interaction episodes which are essential in language learning and acquisition.